Celestial navigation - Pepito, Veronico B. (Valenzuela, Metro Manila : 24k PRINTING CO., INC., 1995)
Celestial Navigation is a highly skills of a navigator's navigating towards the seven seas, this requires a mastery of fixing position with the aid of sextant, cronometer watch and tables for celestial bodies.
Chapter 1. Introduction -- Chapter 2. The Celestial Sphere -- Chapter 3. Time -- Chapter 4. Sight Reduction -- Chapter 5. Navigator's Sextant -- Chapter 6. Star Identification -- Chapter 7. Finding Latitude and Longtitude.
Keywords: NAVIGATIONS -- MARITIME